Telomere-to-telomere genome assembly of a male goat reveals variants associated with cashmere traits - Hui Wu; Ling-Yun Luo; Ya-Hui Zhang; Chong-Yan Zhang; Jia-Hui Huang; Dong-Xin Mo; Li-Ming Zhao; Zhi-Xin Wang; Yi-Chuan Wang; EEr He-Hua; Wen-Lin Bai; Di Han; et al. (Nature Communications)
Abstract A complete goat (Capra hircus) reference genome enhances analyses of genetic variation, thus providing insights into domestication and selection in goats and related species. Here, we assemble a telomere-to-telomere (T2T) gap-free genome (2.86 Gb) from a cashmere goat (T2T-goat1.0), including a Y chromosome of 20.96 Mb. With a base accuracy of >99.999%, T2T-goat1.0 corrects numerous genome-wide structural and base errors in previous assemblies and adds 288.5 Mb of previously unresolved regions and 446 newly assembled genes to the reference genome. We sequence the genomes of five representative goat breeds for PacBio reads, and use T2T-goat1.0 as a reference to identify a total of 63,417 structural variations (SVs) with up to 4711 (7.42%) in the previously unresolved regions. T2T-goat1.0 was applied in population analyses of global wild and domestic goats, which revealed 32,419 SVs and 25,397,794 SNPs, including 870 SVs and 545,026 SNPs in the previously unresolved regions. Also, our analyses reveal a set of selective variants and genes associated with domestication (e.g., NKG2D and ABCC4) and cashmere traits (e.g., ABCC4 and ASIP).